2020
DOI: 10.1038/s41598-020-71709-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of capacitive electromyography biomedical sensor insulated with porous medical bandages

Abstract: A capacitive electromyography (cEMG) biomedical sensor measures the EMG signal from human body through capacitive coupling methodology. It has the flexibility to be insulated by different types of materials. Each type of insulator will yield a unique skin–electrode capacitance which determine the performance of a cEMG biomedical sensor. Most of the insulator being explored are solid and non-breathable which cause perspiration in a long-term EMG measurement process. This research aims to explore the porous medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Nevertheless, there are a number of challenges that need to be tackled throughout the process of EMG monitoring, including motion artifacts, perspiration interference and high impedance. An instance of this phenomenon is the presence of epidermal surface lipids on the electrode, which leads to suboptimal contact between the electrode and the skin (Kim et al, 2020a(Kim et al, , 2020b(Kim et al, , 2020cNg et al, 2020). As a consequence, this creates a potential barrier and diminishes the SNR.…”
Section: Emgmentioning
confidence: 99%
“…Nevertheless, there are a number of challenges that need to be tackled throughout the process of EMG monitoring, including motion artifacts, perspiration interference and high impedance. An instance of this phenomenon is the presence of epidermal surface lipids on the electrode, which leads to suboptimal contact between the electrode and the skin (Kim et al, 2020a(Kim et al, , 2020b(Kim et al, , 2020cNg et al, 2020). As a consequence, this creates a potential barrier and diminishes the SNR.…”
Section: Emgmentioning
confidence: 99%
“…However, several obstacles must be addressed in the EMG monitoring process, such as motion artifacts, sweat, and high impedance [ 55 , 56 ]. For example, epidermal surface lipids contaminate the electrode, resulting in poor contact between the electrode and the skin, a potential barrier, and a lower SNR.…”
Section: Bioelectrical Signalsmentioning
confidence: 99%
“…CC is a non-invasive technology that applies an electric field, and two skin electrodes are aimed at the treatment site. Therefore, electrical energy is induced from one electrode to the other electrode through frequency changes to stimulate the treatment site and achieve the purpose of treatment [ 24 , 25 , 26 ]. Studies have reported that a PEMF, DC, and CC have therapeutic effects on osteoporosis.…”
Section: Introductionmentioning
confidence: 99%